West Nusa Tenggara Tourism Policy Learning Responding to the Covid-19 Pandemic - Muttaqin, M. Zaenul; Bagus Nuari Harmawan (Politeknik Pariwisata NHI Bandung, 2021)
The spread of Covid-19 directly hit the tourism sector in West Nusa Tenggara (NTB). Changes in West Nusa Tenggara tourism conditions require the government to adopt new policy measures to deal with conditions. Local governments in NTB are trying to restore the tourism sector with a social configuration or policy environment. This study explores policy learning in tourism recovery in the West Nusa Tenggara region due to Covid-19. The method used is a literature review with a narrative review approach. The literature analyzed in this study comes entirely from journal articles discussing tourism recovery in NTB due to the Covid-19 pandemic. Policy learning at the micro-level shows that policymakers must absorb the socio-cultural values of the community as a consideration in taking steps to improve tourism. At the meso level, some tourist destinations still find it challenging to get out of the pressure of the pandemic due to limited infrastructure to the preparation of human resources in anticipating the effects of the pandemic. At the macro level, direct intervention from the Ministry of Tourism is needed in three aspects. First, build tourism supporting facilities. Second, various policies are implemented based on Cleanliness, Health, Safety, and Environmental Sustainability (CHSE). Third, tourism recovery involves multi-stakeholder. This study contributes to making a theoretical contribution to policy learning in restoring the tourism sector due to the pandemic. Practically, this study can be a reference for the government in restoring the conditions of various tourist destinations in NTB.